2018
DOI: 10.1002/chem.201706046
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Oxidation Catalysis by a Molecular Barium Vanadium Oxide

Abstract: Aerobic catalytic oxidations are promising routes to replace environmentally harmful oxidants with O in organic syntheses. Here, we report a molecular barium vanadium oxide, [Ba (dmso) V O (NO )] (={Ba V }) as viable homogeneous catalyst for a series of oxidation reactions in N,N-dimethyl formamide solution under oxygen (8 bar). Starting from the model compound 9,10-dihydroanthracene, we report initial dehydrogenation/ aromatization leading to anthracene formation; this intermediate is subsequently oxidized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 40 publications
1
16
0
3
Order By: Relevance
“…This is mainly due to the small ionic radius of vanadium which presents challenges in isolating stable Keggin-and Dawson-type POVs, as well as their corresponding Lacunary derivatives. 51 Seminal contributions into the generation of heteroion-installed polyoxovanadates have been led by Streb [164][165][166][167][168][169][170][171][172][173][174] and others 34,[175][176][177] Fig. 16).…”
Section: Synthesis and Structure Of "Doped" Pov Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…This is mainly due to the small ionic radius of vanadium which presents challenges in isolating stable Keggin-and Dawson-type POVs, as well as their corresponding Lacunary derivatives. 51 Seminal contributions into the generation of heteroion-installed polyoxovanadates have been led by Streb [164][165][166][167][168][169][170][171][172][173][174] and others 34,[175][176][177] Fig. 16).…”
Section: Synthesis and Structure Of "Doped" Pov Clustersmentioning
confidence: 99%
“…This is rather surprising given the extensive literature showing that polyoxometalates can facilitate oxidative chemical transformations, similar to OAT reactions invoked with extended solids. Investigations into this oxidative reactivity of POMs have been extensively studied by Neumann 174,[210][211][212][213][214][215][216][217][218][219] and others, 220 who have shown that POMs can mediate oxidative degradation of organic substrates under ambient reaction conditions. Mechanistic investigations have suggested that the mediation of these transformations with Keggin-type polyoxometalates, such as [PV 2 M 10 O 40 ] n , likely undergoes a mechanism in which oxygen-atom vacancies are required to facilitate the OAT processes (i.e.…”
Section: Atomically Precise Models Of O-atom Vacancies In Rmosmentioning
confidence: 99%
“…Vork urzem wurdejedoch gezeigt, dass der Massentransport des O 2 an der Gas-flüssig-Grenzfläche die katalytische Aktivitätd er POVs stark einschränken kann. [94] [95] Wird das System mit dem Photosensibilisator [Ru(bpy) 3 ] 2+ (bpy = 2,2'-Bipyridin) und dem Oxidationsmittel Peroxodisulfat gekoppelt, dann zeigt das System Wasseroxidation unter Bestrahlung mit sichtbarem Licht. [95] Umsatzzahlen von ca.…”
Section: Aufsätzeunclassified
“…Vanadates have been demonstrated to have many applications in different technical fields, such as optical lasers,e lectrochemistry devices, biology materials, medicine, electronic industry etc. [1][2][3] Especially as ak nown phosphorescent representative, the luminescence of vanadate materials has been intensively investigated in the past years. [4] Rare-earth (RE)i ons-activated vanadate phosphors usually present efficient luminescence even at ambient atmosphere due to the optically active VO 4 groups and the low-site symmetry of the RE activators in the host.…”
Section: Introductionmentioning
confidence: 99%
“…Vanadates have been demonstrated to have many applications in different technical fields, such as optical lasers, electrochemistry devices, biology materials, medicine, electronic industry etc . Especially as a known phosphorescent representative, the luminescence of vanadate materials has been intensively investigated in the past years .…”
Section: Introductionmentioning
confidence: 99%